You don't need a title to be a leader: how anyone, anywhere, can make a positive difference - Sanborn, Mark (Random House Business London, 2007)
Despite popular myth, leaders - whether titled or untitled - aren't born. They learn how to lead. The real test of leadership is, if you had no title or ability to reward or penalize others, could you still get them to follow you? In this powerful follow-up to The Fred Factor, world-renowned motivational speaker Mark Sanborn explains how each of us can be a leader whatever we do - regardless of our title or position. He sets down the key skills that genuine leaders have mastered, and encourages us all to apply them, wherever we may be in the pecking order. Genuine leaders: plan ahead, thinking about where they're heading before they begin; are terrific at communicating and at listening; care about the success of the entire team and look for ways to encourage useful contributions from everyone. By following Mark Sanborn's advice you can take control of your life, seize new opportunities, and maybe even make the world a little better. And you don't need a title to do it